Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Kristalin Ekalestari di Jakarta Selatan - Dimas Wahyu Aryatama; Umar Hanis (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of motivation and work environment both partially and simultaneously on employee performance at PT Kristalin Ekalestari in South Jakarta. The research method used is Quantitative Method. The sampling technique used was saturated with a sample of 60 respondents. Data analysis using Validity Test, Reliability Test, Descriptive Statistical Analysis, Classical Assumption Test, and Hypothesis Test. The results showed that motivation has a significant effect on employee performance, work environment has a significant effect on employee performance, work motivation and work environment have a significant effect on employee performance with the regression equation Y = 9.808 + 0.244X1 + 0.599X2. The correlation coefficient or the level of relationship between the independent variable and the dependent variable is 0.787 The coefficient value is 61.9% and the hypothesis test obtained the value of ????ℎ????????????????????>???????????????????????? or (46.351> 3.16). Thus, H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence between Motivation and Work Environment on Employee Performance of PT Kristalin Ekalestari in South Jakarta.